(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
درست إمكانية إزالة الرصاص باستخدام الزيوليت الطبيعي في منظومة ذات طورين: سائل (مياه ملوثة بالرصاص) – صلب ( زيوليت طبيعي ), وذلك بتابعية العوامل التالية: زمن خلط الطورين, الحجم الحبيبي للطور الصلب, تغير قيم درجة الحموضة pH, تركيز عنصر الكالسيوم كعنصر منافس للمواقع المتاحة للارتباط على الطور الصلب, النسبة V/m كنسبة تمثل حجم الطور المائي على كتلة الطور الصلب وتركيز عنصر الرصاص. بالمقابل, درست إمكانية استخدام الزيوليت الطبيعي كقالب لتوضيب مواد خطرة كالرصاص وذلك بتغيير نوعية المياه ودرجة الحموضة ودرجة الحرارة. تظهر نتائج هذا البحث, أنه, وضمن الشروط التجريبية التالية: زمن خلط يساوي أربع ساعات, خليط من الحجوم الحبيبية, درجة pH اقل من 8, نسبة V/m تساوي 100, تركيز الكالسيوم كعنصر منافس يساوي 20 ppm وتركيز عنصر الرصاص كعنصر ملوث 1000 ppm, فإن نسبة إزالة الرصاص تتراوح بين 60% و99%. من جهة ثانية, تبين نتائج هذا البحث, أن تغير نوعية المياه لا يمارس أي تأثير على مقدرة احتفاظ الزيوليت الطبيعي بالرصاص كنفاية خطرة, في حين تلعب درجة الحموضة تأثيرات طفيفة على هذه المقدرة و كذلك فإن درجات الحرارة المرتفعة تؤثر على قدرة احتفاظ القالب بالرصاص. studied the elimination of lead using natural zeolite by studding the the best conditions to removal lead in a system with two phase: liquid (contaminated water with lead)-solid (natural zeolite), correlation of the following factors: time of mixing phase, granular size of solid phase, change of pH values, concentration of the calcium element as a competitor element for the available sites for occupation on the solid phase, the ratio V/m represents the size of the aqueous phase to the mass of the solid phase and concentration of lead element. On the other hand, the possibility of using natural zeolite as a template for storaging dangerous materials such as lead, has been studied by changing water quality, pH and temperature. The results of this research show that and under the following experimental conditions: time of mixing=4hour, mix of granular size of solid phase, pH< 8, concentration of calcium = 20 ppm,V/m=100 and concentration of lead = 1000 ppm , the rate of lead removal range from 60% to 99%. On the other hand, the results of this research show that changing water quality has no impact on the ability of natural zeolite for storaging lead as a hazardous waste, while pH changes have minor effects on this ability of retention and an effect for the high temperatures on the template was also observed.